AN EXAMINATION OF NEW GENERATION COOPERATIVES IN THE UPPER MIDWEST: SUCCESSES, FAILURES, AND LIMITATIONS. (17th May 2018) - GRASHUIS, Jasper; COOK, Michael
ABSTRACT: A new organizational form, the new generation cooperative (NGC), emerged in the United States during the 1990s as farm producers came together to collectively add value to raw farm commodities. As compared to the traditional cooperative, the NGC facilitates a strong market orientation by defining membership and requiring high supply and equity capital commitments. Approximately 100 such value‐added ventures formed during a period called 'cooperative fever', but public and producer interest dissipated in the 2000s. With secondary data collected from print media publications, we conclude that many of the original NGCs exited by means of bankruptcy or liquidation because of challenges common to most business organizations. However, other failures and conversions of large, successful NGCs also indicate an inherent equity and liquidity constraint, suggesting a limited ability of the organizational form to drive complex and capital‐intensive value‐added ventures. We conclude by raising possible conditions for the future viability of producer‐owned business organizations in the value‐added agri‐food industry.